Medhårs och mothårs: Etnologisk forskning i relation till intern historieskrivning - Arvidsson, Alf (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
When doing cultural history research, the researcher can come across already established opinions of what the history is in a field. Aitologies, lists of heroes and masters, turning point anecdotes and written histories are present as more or less taken for granted within a community. This is a convenient starting-point and background material for a researcher, but can also hide more than it shows by confirming contemporary definitions, power relations, inclusions and exclusions. As an example, I analyse tendencies within Swedish Jazz History by going through interviews made at the Centre for Swedish Folk Music and Jazz Research. A conventional attitude would be to accept the collection as fairly representative: the most important musicians have been interviewed and there is a good sample across different decades. However, in a reading “against the grain” by the use of Katherine Galloway Young’s concepts of Taleworld, storyrealm and interview situation, the interviews stand forward as negotiations of what jazz styles, what musicians and what qualities should be included in the Swedish jazz field and what is to be left out. In this case, foreign born musicians and women musicians are marginalized in Swedish jazz history, as well as styles that can seem to be too commercial. The musicians chosen are either stars, or witnesses to the stars. Working against the grain of the emic Swedish Jazz history is to problematize what has been outdefined and how, to ask counterfactual questions on what could have happened if other discourses had dominated, and reflect on new questions to ask, new definitions of the research object, and the need for new and/or revised documentation.